Contralateral seventh cervical nerve transfer for central spastic arm paralysis: a systematic review and meta-analysis - Luo, WenMiao; Yan, ZhengCun; Guo, Yu; Xu, Ji; Zhang, Heng-Zhu (Frontiers in Neurology, 2023)
The specific benefits of a contralateral cervical 7 nerve transplant in people with spastic paralysis of the upper extremity caused by cerebral nerve injury are unclear. To evaluate the efficacy and safety of contralateral C7 nerve transfer for central spastic paralysis of the upper extremity, we conducted a comprehensive literature search and meta-analysis.Materials and Methods: PRISMA guidelines were used to search the databases for papers comparing the efficacy of contralateral cervical 7 nerve transfer vs. rehabilitation treatment from January 2010 to August 2022. The finishing indications were expressed using SMD ± Mean. A meta-analysis was used to assess the recovery of motor function in the paralyzed upper extremity.11The meta-analysis included three publications. One of the publications offers information about RCTs and non-RCTs. A total of 384 paralyzed patients were included, including 192 who underwent CC7 transfer and 192 who received rehabilitation. Results from all patients were combined and revealed that patients who had CC7 transfer may have regained greater motor function in the Fugl-Meyer score (SMD 3.52 ， 95%CI= 3.19~3.84, P < 0.00001) and had superior improvement in range of motion compared to the rehabilitation group (SMD 2.88 ， 95%CI= 2.4718 3.29 ， P < 0.00001).In addition, the spasticity in the paralyzed upper extremity significantly improved in patients with CC7 transfer (SMD -1.42 ，95%CI= -1.6020 -1.25, P < 0.00001).Our findings suggested that a contralateral C7 nerve transfer, which has no additional adverse effects on the healthy upper limb, is a preferable method to restore motor function.